THE INFLUENCE OF UNDERWRITER REPUTATION, AUDITOR REPUTATION, COMPANY SIZE AND COMPANY AGE ON UNDERPRICING IPO FOR COMPANIES LISTED IN INDONESIA STOCK EXCHANGE PERIOD 2008-2013 - Ririn Salfida; Kencana Dewi; Mukhtaruddin Mukhtaruddin (AKUNTABILITAS, 2014)
This study aims to analyze the influence of non-accounting factors of the underpricing  IPO  stock  in  Indonesia  Stock  Exchange.  In  this  study,  the independent   variables   used   are   underwriter   reputation,   auditor   reputation, company size and company age, while the dependent variable in this study is the initial return.The data used in this study are secondary data from the Indonesia Stock Exchange and the Indonesian Capital Market Directory (ICMD) from 2008 to 2013. Samples were selected using purposive sampling method. From 135 companies that conduct an IPO in 2008-2013, there are 85 companies that meet predetermined criteria. The method of data analysis used in this study is multiple linear regression. The analysis showed that company size and company age significantly influences   the   underpricing   of   IPO   with   negative   direction.   While   the underwriter's reputation and the reputation of the auditor no significant effect on IPO underpricing. Limitations in this research that the criteria used to measure underwriter  reputation  and  the  reputation  of  the  auditor  only  use  the  data tabulation  of  the  total  listed  companies  and  the  data  sample  in  2013  is  stilldifficult to obtain because it has not published by the Indonesia Stock Exchange.